Losing Face, Finding Love? The Fate of Facially Disfigured Soldiers in Narratives of the First World War - Gehrhardt, Marjorie (Litteraria Copernicana, 2018)
Changes in warfare, new weaponry and the absence of protective equipment meant that facial injuries were common during the First World War. The negative perceptions surrounding such wounds, described as “the worst loss of all” (Anon 1918), and the widespread expectation that facially disfigured combatants would be outcast from society, partly explain why facially injured combatants are rarely represented in wartime and interwar literature. This article however shows that the way in which the wounded combatants’ fates are portrayed in fiction differs significantly from these bleak predictions. Drawing upon popular fiction such as Florence Ethel Mills Young’s Beatrice Ashleigh (1918) and Muriel Hine’s The Flight (1922), this article explores literary representations of disfigurement and depictions of the physical, psychological and social consequences of disfiguring injuries. In a context in which anxieties over the masculinity of disabled veterans were increasing, the depictions of fictional mutilated ex-servicemen’s reintegration into society are discussed with special emphasis on the agency of women, who appear to have the power, in Macdonald’s words, to make men “whole” again (Macdonald 2016: 54).